Penerapan Media Tangram Pada Materi Bangun Datar Untuk Meningkatkan Hasil Belajar Matematika Siswa kelas IV SDN 13 Sitiung - Ulfa, Melia (PGSD Universitas Muhammadiyah Cirebon, 2025)
This research is based on students low scores learning outcomes in learning two-dimensional shapes at grade IV SDN 13 Sitiung. This is because students consider mathematics a difficult subject, in the process of learning mathematics, there is less use of media to convey messages and facilitate understanding of concepts and memory for students so that learning becomes monotonous and boring. On the other hand, there is a tendency that students are quite passive, students' willingness to ask questions and low enthusiasm for learning when participating in the learning process so that students do not understand the material which results in low learning outcomes. The purpose of this study was to determine the improvement in learning outcomes through tangram media in Mathematics subjects of grade IV of SDN Sitiung 13 Academic Year 2024/2025 on two-dimensional shapes. This type of research was Classroom Action Research (CAR), a type of research conducted by the teacher in her own classrooms to solve learning problems and improve the quality of teaching. With 20 students as subjects, this research was conducted for 2 cycles, each cycle was conducted 2 meeting with the stages of planning, implementation, observation and reflection. The results of this study shows that the learning outcomes of students in cycle I are 55% then increased by 40% because in cycle II it increased to 95%. Based on the results of this study, it can be concluded that the use of media can improve the learning outcomes of students in the Mathematics subject of class IV of SD Negeri 13 Sitiung in the 2024/2025 Academic Year